Unpacking a Telemedical Takeover: Recommendations for Improving the Sustainability and Usage of Telemedicine Post-COVID-19. Issue 2 (23rd April 2022) - Kaundinya, Trisha; Agrawal, Rishi
Abstract : Telemedicine technology and regulation have been steadily growing over the last 2 decades. Prior to the coronavirus disease-2019 (COVID-19) pandemic, the availability of telemedicine in health systems and coverage of telemedicine were variable. Sudden and improved access to telemedicine was propelled by the COVID-19 pandemic, during which governments, insurers, and health systems ramped up telemedical utilization with short-term exceptions and waivers. As in-person care opportunities open back up, the presence of telemedicine is not receding and thus its widespread adoption needs to be facilitated outside pandemic-specific conditions. Long-term funding for telemedicine acquisition, centralized electronic health records, extended waivers related to telemedicine coverage and use, a Medicaid expansion that involves parity in telemedicine and in-person care, a nationalized licensure system, and an assessment of what types of care settings can and cannot utilize telemedicine are necessary recommendations to improve the sustainability of telemedicine after the pandemic.